THE SIGNIFICANCE OF REFORMS IN THE HIGHER EDUCATION SYSTEM IN UZBEKISTAN (Marketing Journal, 2026)
This scientific article provides a comprehensive analysis of the content and socio - economic significance of the reforms implemented in the higher education system of Uzbekistan since 2016. The study examines the key priorities of state policy in higher education, as well as trends in the expansion of access to higher education, the growth in the number of higher education institutions, and student enrollment based on official statistical data. Through a review of international academic literature, the role of education in human capital development and economic growth is substantiated. In addition, reforms in the higher education systems of Japan and Germany are analyzed, and elements of their experience that can be adapted to the context of Uzbekistan are identified. № 1 -SON YANVA R, 202 6-YIL 258
Keywords: higher education system; educational reforms; state policy; human capital; economic development; higher education coverage; higher education institutions; student enrollment; international experience; Japanese education system; German education system; qua lity of education